2017
DOI: 10.31231/osf.io/7ytr9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential changes in self-reported aspects of interoceptive awareness through 3 months of contemplative training

Abstract: Interoceptive body awareness (IA) is crucial for psychological well-being and plays an important role in many contemplative traditions. However, until recently, standardized selfreport measures of IA were scarce, not comprehensive, and the effects of interoceptive training on such measures were largely unknown. The Multidimensional Assessment of Interoceptive Awareness (MAIA) questionnaire measures IA with eight different scales. In the current study, we investigated whether and how these different aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…Furthermore, we did not consistently observe relationships between practice intensity (how often or long participants practiced) and changes in HBPa (only in TC2 during the Presence module). This is in accordance with an earlier study in the context of the ReSource Project (Bornemann, Herbert, Mehling, & Singer, ) as well as several previous longitudinal studies of contemplative practice (Carmody & Baer, ; Hofmann, Sawyer, Witt, & Oh, ; Jensen, Vangkilde, Frokjaer, & Hasselbalch, ; but also see Carmody & Baer, ; Pace et al, ; Rosenzweig et al, ; Shapiro, Oman, Thoresen, Plante, & Flinders, ). We assume that variance in practice intensity was too small to demonstrate dose‐dependent effects due to the generally high compliance of participants in the ReSource Project.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we did not consistently observe relationships between practice intensity (how often or long participants practiced) and changes in HBPa (only in TC2 during the Presence module). This is in accordance with an earlier study in the context of the ReSource Project (Bornemann, Herbert, Mehling, & Singer, ) as well as several previous longitudinal studies of contemplative practice (Carmody & Baer, ; Hofmann, Sawyer, Witt, & Oh, ; Jensen, Vangkilde, Frokjaer, & Hasselbalch, ; but also see Carmody & Baer, ; Pace et al, ; Rosenzweig et al, ; Shapiro, Oman, Thoresen, Plante, & Flinders, ). We assume that variance in practice intensity was too small to demonstrate dose‐dependent effects due to the generally high compliance of participants in the ReSource Project.…”
Section: Discussionsupporting
confidence: 92%
“…Also consistent with prior research (Bornemann, Herbert, Mehling, & Singer, ; Mehling et al, , ; Valenzuela‐Moguillansky & Reyes‐Reyes, ), we found that four out of eight subscales demonstrated good internal consistency. In addition, questionable internal consistency of the Not Worrying and Not Distracting subscales is in line with numerous similar findings that have prompted Mehling and colleagues () to continue to refine these subscales.…”
Section: Discussionsupporting
confidence: 91%
“…22 Plausible mechanisms include craving (eg, for palatable foods and sedentary activities), 19,20,22 stress response (particularly related to diabetes risk factors, such as impacts of stress on palatable food consumption), 23 sense of control (eg, a person’s sense of efficacy in carrying out goals related to diabetes prevention, such as diet or physical activity regimen adherence), 18 and awareness of present moment experiences (eg, including body awareness of how the body feels after consuming certain types/amounts of foods and engaging in physical activities). 2426 Observational studies suggest that lipids, hypertension, smoking, depression and socioeconomic status also can improve risk prediction for type 2 diabetes, although their causal role in the development of type 2 diabetes is less clear. 14,27 These may be additional plausible mechanisms of how mindfulness could influence glucose regulation.…”
mentioning
confidence: 99%